Implementation of E-Commerce Website to Improve Marketing of Msmes Products: A Case Study of Kemang Village, Cianjur Regency - Ginanjar Nugraha; Khalby, Muhamad; Ratnasari; Afriliani, Sri; Faisal , Muhammad Ikhsan; Adnan, Krisna (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
The development of digital technology provides opportunities for MSMEs to expand their markets through e-commerce platforms. However, in Kemang Village, Cianjur Regency, many MSMEs still rely on conventional marketing, limiting their reach. This study aims to implement an e-commerce website to improve the marketing of MSME products in Kemang Village. The method used was a qualitative approach with the stages of needs analysis, system design, website development, and evaluation. The results show that the developed e-commerce website can help MSMEs promote their products online, increase visibility, and facilitate transactions with consumers. With this platform, it is hoped that MSMEs in Kemang Village can compete in the digital market and increase their income.